Unconfined Groundwater Storage Change over the Greater Chao Phraya River Basin - Kruy, Phanith; Ruangrassamee, Piyatida (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
Groundwater monitoring network is essential to monitor groundwater levels and usage, however, it requires relatively high capital and human resources. Advanced land surface modeling and data assimilation techniques using ground based observations and satellite products provide complementary information concerning space and time for groundwater change Global Land Data Assimilation System version 2.2 (GLDA-v2.2) provides daily groundwater storage (GWS) products from 2003 to present for unconfined aquifers. This study aims to analyze monthly groundwater storage change over the Greater Chao Phraya River basin between 2009 to 2018 using data from the monitoring wells with their screen depth less than 30 meters for validation. The Mann-Kendall test was used to analyze GWS trends. Based on the GWS from GLDAS-v2.2 the GWS in the transition zone from the upper to the lower part of the Greater Chao Phraya River basin (around Kamphaeng Phet, Phichit, Sukhothai, and Nakhon Sawan provinces) is lower compared to the GWS in the northern part of the Greater Chao Phraya River basin. The estimated GWS from the observed water table level is based on the water table fluctuation (WTF) method (GWSWTF). The correlation coefficient between GWSGLDAS and GWSWTF is greater than 0.7. Overall, GWSGLDAS is underestimated compared to GWSWTF. According to the Mann-Kendall Test, the groundwater storage has significant change (p < 0.05) in most of the Greater Chao Phraya River basin except during the transition period (TS). The GWS in the northern part of the Greater Chao Phraya River basin around Chiang Mai, Lamphun, Lampang, Phrae, and Phayao provinces shows higher depletion compared to the lower part of the Greater Chao Phraya River basin. For seasonal change, the highest depletion occurred during the southwest monsoon (SW) with the depletion rate of 3.4 mm/month, followed by depletion during Northeast monsoon (NE) which is 3.0 mm/month. For the transition period (TS), the depletion rate is 2.5 mm/month. The analysis of monthly data shows that the highest annual GWS depletion is 1.2 mm/month. The increasing trend occurred around Samut Sakhon, Bangkok, Pathum Thani, and Nakhon Nayok provinces. The rate of increasing trend in those provinces is up to 0.50 mm/month.